The satisfaction of patients with breast cancer undergone immediate reconstruction with implant and the effect of radiotherapy - Yıldırım Altınok, Ayşe; Şenel Beşe, Nuran; Kara, Halil; Yazar, Şükrü; Ünal, Cihan (Termedia Publishing House Ltd., 2018)
Aim of the study: Postmastectomy reconstructive surgery for cosmetic satisfaction of patients is rapidly increasing. Postoperative complications such as infection, capsular contracture, implant loss are more common in patients who receive adjuvant radiotherapy (RT) than those who do not. Satisfaction levels in patients is still a controversial issue. Therefore, we wanted to investigate our patient population for the effects of RT and planned a study evaluating the satisfaction rates of our patients who received implants. Material and methods: Seventy five breast cancer patients who went through mastectomy and went through reconstruction using expanders or silicone implants were surveyed. Complication and cosmetic satisfaction rates were separately compared between irradiated and nonirradiated implants. Responses of 46 patients who answered the survey were analyzed using chi(2) test and Mann Whitney U test. p < 0.05 was considered statistically significant. Results: Thirty-one of the patients received adjuvant RT and 15 did not receive RT (NRT). There was no difference between the RT and NRT groups in the terms of touch, size, shape of silicones, pain and satisfaction level in look of clothing. Only satisfaction in symmetry was significantly lower in the RT group than in the NRT group (p = 0.02). Additionally, patients receiving chemotherapy were less satisfied with silicone size than those who did not (p = 0.02). Conclusion: We did not find negative effects, other than symmetry, of adjuvant radiotherapy in breast cancer patients who underwent reconstructive surgery in terms of cosmetic satisfaction.
WOS: 000431715800005
PubMed ID: 29692660
Keywords: Immediate Implant; Radiotherapy; Patient Satisfaction